Contezolid, a novel oxazolidinone antibiotic, may improve drug-related thrombocytopenia in clinical antibacterial treatment - Li, Bi; Liu, Ying; Luo, Jiaqi; Cai, Yun; Chen, Mengli; Wang, Tianlin (Frontiers in Pharmacology, 2023)
One of the major limitations in the clinical use of existing oxazolidinone antibiotics is their characteristic adverse reactions, in particular thrombocytopenia. In anti-infective treatment, if patients are suspected of having drug-induced thrombocytopenia, the first step is to immediately discontinue the offending drug. Even in patients with severe infections, the antibacterial drug may need to be changed or the antibacterial treatment may need to be discontinued because thrombocytopenia may have a more serious clinical prognosis. In addition, if the patient needs to continue antibacterial treatment after discharge, the lack of conditions for monitoring platelet levels may also pose hidden dangers to the patient. Contezolid is an orally administered oxazolidinone antibacterial agent approved by the National Medical Products Administration of China in 2021. We found that contezolid may have an improved safety profile with a significantly reduced potential for myelosuppression based on the results of our observational clinical study. In this article, we review the advantages of contezolid as a new oxazolidinone antibiotic and describe three typical clinical cases of patients who experienced drug-induced thrombocytopenia after using linezolid. The platelet levels of these different patients were all significantly improved to varying degrees after initiation of contezolid treatment.